Results of an Evaluation of Therapeutic Residential Groups for Adolescents in Berlin. (July 2020) - Wesenberg, Sandra; Frank, Christina; de Andrade, Marilena; Weber, Miriam; Rosemeier, Claus-Peter; Krause-Lanius, Bert; Gahleitner, Silke B.
In the last few years, a large amount of research have been done in the field of youth care services. However, there is still a substantial need for empirical findings, especially on institutions with specific missions such as therapeutic residential groups for young people. This article grew out of cooperation between practitioners and researchers and presents the results of a German study entitled "Process Evaluation of Therapeutic Residential Groups for Young People" (TRGs). The main research question of the evaluation study was whether the treatment in the TRGs is specifically stabilizing, protective, and, above all, effective in dealing with young people with severe problems. The study employs multiple methodologies (qualitative and quantitative procedures) to obtain a satisfactorily comprehensive analysis of both outcome and process quality. The article presents selected results from the quantitative part of the study and the qualitative interview study and discusses them considering recent research in the field of child and adolescent care services.